A new station for the endangered fern Woodwardia radicans (L.) Sm. (Blechnaceae) in Northern Campania (Italy) - Croce, Antonio (BORNH Bulletin of Regional Natural History, 2021)
The thermophilous fern Woodwardia radicans, is an iconic species of the Southern Italian flora. This species, endemic to Southern Europe and Macaronesia, likely represents a Macaronesian relict in Europe. Here, I describe a new station for this endangered species, in the Northern part of the Campania region (Southern Italy), that extends northward the distribution limit in the Italian peninsula. The site is located along the stream Savone delle Ferriere, on the Roccamonfina Volcano, within the Roccamonfina-Foce Garigliano Regional Park. The vegetation of the area shows the same feature of other Woodwardia radicans communities in Italy and grows on the very steep slopes in the lower part of the gorge of the stream, in a section characterized by huge waterfalls. The new station extends both the area of occupancy (AOO) and the extent of occurrence (EOO), two parameters used to assess the extinction risk by IUCN. In addition, new observations for other fern species, which are rare at regional level (as Pteris cretica, Struthiopteris spicant and Dryopteris affinis subsp. affinis), were reported.